2001
DOI: 10.1074/jbc.m103523200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Single-stranded DNA-binding Proteins from Mycobacteria

Abstract: Single-stranded DNA-binding proteins (SSB) play an important role in most aspects of DNA metabolism including DNA replication, repair, and recombination. We report here the identification and characterization of SSB proteins of Mycobacterium smegmatis and Mycobacterium tuberculosis. Sequence comparison of M. smegmatis SSB revealed that it is homologous to M. tuberculosis SSB, except for a small spacer connecting the larger amino-terminal domain with the extreme carboxyl-terminal tail. The purified SSB proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Polyclonal antibodies against EcRecA and M. tuberculosis RecX were generated in rabbits. Anti-EcRecA antibodies cross-reacted with MtRecA (4), as well as MsRecA (14). Anti-RecX antibodies cross-reacted with purified RecX, as well as a 19-kDa protein in the cell lysates of M. tuberculosis and M. smegmatis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyclonal antibodies against EcRecA and M. tuberculosis RecX were generated in rabbits. Anti-EcRecA antibodies cross-reacted with MtRecA (4), as well as MsRecA (14). Anti-RecX antibodies cross-reacted with purified RecX, as well as a 19-kDa protein in the cell lysates of M. tuberculosis and M. smegmatis.…”
Section: Methodsmentioning
confidence: 99%
“…Under these conditions, 10 ng of [ 3 H]ssDNA incubated with the lysates was completely degraded to acid-soluble nucleotide residues by 10 g of DNaseI (data not shown). Immunoprecipitation and immunoblotting experiments were performed as described (14). An aliquot of cell lysate (0.5-0.75 mg protein) in 20 mM Tris⅐HCl (pH 7.5)͞0.2 M NaCl͞1 mM ATP (buffer TNA) was incubated with anti-RecA or anti-RecX antibodies at 4°C for 6 h, and then with 50 l of slurry of protein A-Sepharose for an additional 2 h. Immunoprecipitates were collected by centrifugation, washed six times with TNA buffer containing 0.1% Triton X-100, stained with appropriate primary and secondary antibody, and visualized by chemiluminescence (14,20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strand transfer mediated by the gene 4 helicase readily occurs in the presence of gp2.5 (14). T7 gp2.5, E. coli SSB protein, and T4 gene 32 protein all have an acidic C terminus of which a number of studies shown are essential for the protein-protein interactions observed in vitro (6,7,13,(15)(16)(17)(18)(19). A truncated gp2.5, gp2.5-⌬21C, lacking the 21 C-terminal residues cannot support T7 growth, and the purified protein cannot form dimers or physically interact with T7 DNA polymerase or gp4 (6).…”
mentioning
confidence: 99%
“…These strands form two additional clamp-like structures in the homotetrameric SSB which contribute to the overall stability of the quaternary structure of SSB (18,21). It is thought that the mode of DNA binding of actinobacterial SSBs is different from that of EcoSSB partly on account of the difference in the shape of the tetramers (22,23).…”
Section: The Ct Domain Terminates With a Conserved Acidic Hexapeptimentioning
confidence: 99%